The antifungal activity of Pancratium maritimum - (:unkn) unknown (ELSEVIER SCIENCE BV, 1999)
The methanol extract of P. maritimum bulbs, though devoid of antibacterial activity, showed interesting antifungal activity against four Candida species, being, however, ineffective against C. albicans. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: Pancratium maritimum; antifungal activity